2016
DOI: 10.1097/mnh.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the kidney using magnetic resonance techniques

Abstract: (2016) Imaging the kidney using magnetic resonance techniques: structure to function. Current Opinion in Nephrology and Hypertension, 25 (6). pp. 487-493. ISSN 1473-6543 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/39487/1/REVIEW_RENAL_EPRINTS_ALL.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
0
21
0
4
Order By: Relevance
“…4,5 Renal biopsy is the standard method for assessing renal fibrosis. Several MRI techniques, [9][10][11] including blood oxygenation-level-dependent (BOLD) imaging and diffusion weighted imaging (DWI), have also been used to assess renal fibrosis. 6 Ultrasound has shown some promising results in measuring renal cortical stiffness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Renal biopsy is the standard method for assessing renal fibrosis. Several MRI techniques, [9][10][11] including blood oxygenation-level-dependent (BOLD) imaging and diffusion weighted imaging (DWI), have also been used to assess renal fibrosis. 6 Ultrasound has shown some promising results in measuring renal cortical stiffness.…”
mentioning
confidence: 99%
“…7,8 However, the results were controversial and influenced by blood pressure and intra-and interobserver variability. Several MRI techniques, [9][10][11] including blood oxygenation-level-dependent (BOLD) imaging and diffusion weighted imaging (DWI), have also been used to assess renal fibrosis. However, the results for DWI were controversial.…”
mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI), including T2‐weighted imaging (T2WI), T2 * W imaging, arterial spin labelling, blood oxygen level‐dependency (BOLD) imaging and diffusion‐weighted imaging, provides promising new techniques for evaluation of renal pathophysiology (Mahmoud et al . ; Zhou et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of magnetic resonance imaging (MRI) technology, studies utilizing functional (fMRI), including diffusion‐weighted imaging (DWI) and perfusion MRI with arterial spin labeling (ASL), have been employed in clinical applications …”
mentioning
confidence: 99%
“…3 With the development of magnetic resonance imaging (MRI) technology, studies utilizing functional (fMRI), including diffusion-weighted imaging (DWI) and perfusion MRI with arterial spin labeling (ASL), have been employed in clinical applications. 4 DWI reflects the random Brownian motion of water molecules in tissues and measures the extent and direction of localized confinement, which indirectly reflects changes in the microstructure. Some reports have shown that renal apparent diffusion coefficient (ADC) values can be used as a sensitive index of the degree of fibrosis.…”
mentioning
confidence: 99%